Evaluation the Active Substances of Extracts of Syzygium Aromaticum Plant Flower Buds on Enterobius Vermicularis: In Vitro Study - Al-Taei , Alaa hamady obeid Hassan; Al-Sultani , Assel Kareem; Mousawi, Heyam G. Al (American Journal of Biology and Natural Sciences, 2025)
The flower bud of the Syzygium aromaticum plant exemplifies has the medical significance and it is comprise a number of active and lively compound .Present investigation was done to demonstrate the impact of cold and hot aqueous extracts of S. aromaticum (commonly named as Cloves) flower buds in paralysis and death of Enterobius vermicularis in vitro and detect utmost effective secondary compound (alkaloid, terpenoids and phenolics) of Cloves for analysis by GC-MS. Current findings appear that hot aqueous extract have a high influential where its arithmetical rate for paralysis and death of E. vermicularis about 373.08min for paralysis and 465.50min for death, with clear significance differences. Regarding the outcome of secondary compounds of S. aromaticum flower buds, the current findings revealed that raised impacts for terpenoid compounds extract on worms in the concentration (150 µg/ml), its cause paralysis and death of worms at 7.00 along with12.00 min, respectively, followed by alkaloid compounds that cause paralysis at 11.00 min and death of worms at 15.00min. Regarding to phenolics compounds, its cause the paralysis at 28.00 min and death of worms at 45.00 min with significance differences. The drug Ivermectin causes paralysis at 48.00 min and death at 67.0 min pinworms in the concentration (150 µg/ml), with a high impact and with significance differences. In context of GC/MS technique, its demonstrated that S. aromaticum flower buds contain eugenol , eugenyl acetate, -caryophyllene, and –humulene.